Varying flow division forced by streamflow and tidal force in bifurcation channels in the Pearl River Delta, South China - Yongjun Fang; Xianwei Wang; Huan Liu; Jie Ren; Peiqing Yuan; Yazhou Ning; Xiangqiu Zhang (Geomatics, Natural Hazards & Risk)
River bifurcations are crucial in distributing water, sediment, and flood hazards within river networks. This study established an idealized Delft3D model to investigate the individual and combined impacts of streamflow, tidal amplitude, and river length on flow division, using the Tianhe/Nanhua bifurcation in the Pearl River Delta (PRD) as a case study. The results indicate that flow division is primarily controlled by tidal dynamics during the dry season, whereas streamflow and river length play a dominant role in the wet season, especially during flood periods. A higher tidal amplitude in one branch inhibits flow division, while a shorter branch length enhances flood discharge. Specifically, the Donghai Waterway experiences higher tidal amplitudes at its outlet compared to the Modaomen Waterway, leading to reduced flow division in the dry season. However, during the wet season and flood events, increased streamflow suppresses tidal influence, and the shorter flow path in the Donghai Waterway generates a steeper water surface slope, facilitating greater flow division and contributing to flood mitigation. These findings provide valuable insights for water resource management and flood risk mitigation in the PRD and other river bifurcations with similar geometric and tidal characteristics.